THE COMPARISON OF HEALTH STATUS AND INDEPENDENCE BETWEEN THE ELDERLY IN THE NURSING HOMES AND LIVING WITH FAMILY - Setyowati, Retno; Musfiroh, Mujahidatul; Yuliadi, Istar; Sudibyo, Desiderius Priyo; Utami, Trisni (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2023)
Background: The elderly period is a gift in human life because not all humans can experience this period. The elderly period experience changes in anatomical and physiological functions, so the elderly are very vulnerable to health problems. Many factors cause health problems in the elderly, including decreased function of the elderly and elderly health problems that can affect the independence of the elderly in carrying out daily activities. This study aims to describe the health status and independence of the elderly in nursing homes and living with their families.Method: This research is a descriptive analytic study with an elderly population. The number of respondents in this study were 19 elderly living in nursing home and 13 elderly living with their families. Data collection was carried out at one time, which are: measuring blood pressure, blood sugar levels, blood cholesterol, blood uric acid, and the independence of the elderly.Result: The results showed that the health status of the elderly living in nursing homes was 19 people (100%) had normal blood sugar levels, 5 people (26%) had normal cholesterol levels, 8 people (42%) had normal uric acid levels, 9 people (47 %) had normal blood pressure, and independence shows that 10 people (53%) had the independence to carry out daily activities. The results of research at the elderly post for the data collection on the elderly living at home showed that 27 people (87%) had normal blood sugar levels, 16 people (52%) had normal cholesterol levels, 18 people (58%) had normal uric acid levels, 18 people (58%) had normal blood pressure, and independence showed that 31 people (100%) had the independence to do their daily activities. There are differences in the health status and independence of the elderly who live in nursing homes and those who live with their families.Conclusion: The elderly who live with their family have better health and independence status than the elderly who live in nursing homes. For this reason, efforts are needed to improve the health status and independence of the elderly at nursing homes by holding regular health checks and practicing activities that can stimulate the independence of the elderly.